Changes of snoring sound after relocation pharyngoplasty for obstructive sleep apnoea: the surgery reduces mean intensity in snoring which correlates well with apnoea–hypopnoea index. (April 2015) - Li, H.Y.; Lee, L.A.; Yu, J.F.; Lo, Y.L.; Chen, N.H.; Fang, T.J.; Hsin, L.J.; Lin, W.N.; Huang, C.G.; Cheng, W.N.
<x xml:space="preserve">Abstract</x> Objective To investigate objective changes of snoring after surgery in patients with obstructive sleep apnoea (OSA) and correlate these with changes in the apnoea–hypopnoea index (AHI). Design Prospective case series. Setting A novel measurement, Snore Map, was used to analyse full‐night snore sounds in terms of the maximal/mean intensity, peak/mean frequency, snoring index and energy type (Snore Map type, 0–4). Snore sound was classified into three bands according to frequency energy spectrum: B1 (40–300 Hz), B2 (301–850 Hz) and B3 (851–2000 Hz). Participants Thirty‐four male and two female OSA patients (mean age, 39 years; mean AHI, 53.1/h; mean body mass index, 26.8 kg/m2) with favourable anatomic structure were consecutively enrolled. Main outcome measures Parameters of polysomnographies and Snore Maps at baseline and six months after operation were compared. Statistical significance was set at P < 0.05. Results Thirty‐two patients completed this study. The mean reduction in the total‐snoring index was insignificant but there were significant decreases in total mean intensity, total peak frequency, total mean frequency and Snore Map type after surgery. There were also significant decreases in the mean intensity in all three bands, the snoring index in B2/B3 and the mean frequency in B1 postoperatively. Changes in the total mean intensity, total mean frequency, B2 mean intensity and B3 snoring index positively correlated with change in the AHI. Conclusions Relocation pharyngoplasty significantly decreases both the snoring sound intensity and snoring frequency. These reductions are directly proportional to the improvement of OSA.